1985
DOI: 10.1111/j.1096-3642.1985.tb01804.x
|View full text |Cite
|
Sign up to set email alerts
|

A revision of the genus Prionospio Malmgren, with special emphasis on species from the Atlantic Ocean, and new records of species belonging to the genera Apoprionospio Foster and Paraprionospio Caullery (Polychaeta, Annelida, Spionidae)

Abstract: Several generic schemes used in classifying species belonging to Prionospio Malmgren, 1867 sensu lato have been reviewed; three taxa have been retained at the generic level, and three additional taxa at the subgeneric level. The following genera and subgenera are recognized: Prionospio Malmgren, 1867, including the subgenera Minuspio Foster, 1971, Aquilaspio Foster, 1971 and Prionospio Malmgren (sensu striclo); Apoprionospio Foster, 1969, and Paraprionospio Caullery, 1914. Prionospio sensu lata includes specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
7

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 32 publications
3
46
1
7
Order By: Relevance
“…Historically treated together and referred to as a generic Prionospio complex, for a long time the genus was not explicitly defined and no single character or group of characters was suggested to support its monophyly. Systematic treatments of the complex were overviewed by Foster (1971), Blake & Kudenov (1978), Maciolek (1985), Wilson (1990), Blake (1996), and Sigvaldadóttir (1998). Different generic breakdowns of the complex were suggested by various authors based on different suits of external morphological characteristics of adults and ideas about their weight for taxonomy.…”
Section: Dipolydora Verrill 1881mentioning
confidence: 99%
“…Historically treated together and referred to as a generic Prionospio complex, for a long time the genus was not explicitly defined and no single character or group of characters was suggested to support its monophyly. Systematic treatments of the complex were overviewed by Foster (1971), Blake & Kudenov (1978), Maciolek (1985), Wilson (1990), Blake (1996), and Sigvaldadóttir (1998). Different generic breakdowns of the complex were suggested by various authors based on different suits of external morphological characteristics of adults and ideas about their weight for taxonomy.…”
Section: Dipolydora Verrill 1881mentioning
confidence: 99%
“…The spionid polychaete Paraprionospio pinnata (Ehlers, 1901) has been reported not only from the Mediterranean (BELLAN, 1964;DIAPOULIS & BOGDANOS, 1983;ERGEN, 1992;REDONDO & SAN MART N, 1997;SIMBOURA & NICOLAIDOU, 2001;ERGEN et al, 2002ERGEN et al, , 2006INAR, 2005;DO AN et al, 2005) but also from various temperate and tropical waters in the world (e.g., FAUVEL, 1932;WESENBERG-LUND, 1949;HARTMAN, 1960;DAY, 1961;IMAJIMA & HARTMAN, 1964;HARTMANN-SCHRÖDER, 1965), resulting in it gaining recognition as a cosmopolitan species (LIGHT, 1978;MACIOLEK, 1985). FOSTER (1971) demonstrated that P. pinnata is a monotypic species which belongs to the genus Paraprionospio Caullery, 1914.…”
Section: Introductionmentioning
confidence: 99%
“…90); 0.02 mm (Figs 91-9.3 Reported to be cosmopolitan (e.g. Maciolek, 1985) but all records require confirmation.…”
Section: Introductionmentioning
confidence: 99%